Removalof C02 from Natural Gas with the Presence of Heavy Hydrocarbon Using Membrane Process - JUSOH, NORWAHYU (2013)
The demand for membrane processes particularly in offshore separations has driven the application of membrane towards harsh separation condition. Heavy hydrocarbon is one of the major impurities in the natural gas, yet the understanding of its effect towards the performance of bulk C02 separation using membrane is found to be limited. Hence, the objective of the study is to investigate the separation performance of commercial membrane in removing bulk carbon dioxide from methane with the presence of heavy hydrocarbon (pentane) under various operating conditions. Feed pressure, temperature and concentration were varied to study the separation performance under dry condition (C02-CH4 mixture) and wet condition (CO2-CH4- pentane).